The Role of the Class I Immigration Office of TPI Yogyakarta in preventing illegal Indonesian migrant workers based on Law Number 6 of 2011 - Cristenia Gracia Theis; Walid Jumlad (CV. Rayyan Dwi Bharata, 2022)
The role of the Class I Immigration Office of TPI Yogyakarta in preventing Illegal Indonesian Migrant Workers based on law number 6 of 2011. This is against the background of the large number of unemployed people who make Migrant Workers willing to work anything to be able to continue life. One of the solutions is to become an Indonesian Migrant Worker, because of the large demand for migrant workers from abroad and also the large number of people who want to become migrant workers with convoluted and expensive immigration procedures that make these prospective Indonesian Migrant Workers prefer to become Illegal Indonesian Migrant Workers. The research uses qualitative methods and data processing using interview techniques, field observations and document and literature studies, namely collecting data by systematic observation and recording directly at the research site. One of the efforts made to anticipate the misuse of purposes and objectives in the process of making Travel Documents of the Republic of Indonesia (DPRI) is to select and avoid the issuance of Travel Documents of the Republic of Indonesia with the intention of family visits, tourist visits to countries receiving Indonesian Migrant Workers, in this case the provision of Travel Documents of the Republic of Indonesia for prospective migrant workers should be in accordance with the provisions of the regulations applicable legislation. What is meant here is that the requirements in applying for a Travel Document of the Republic of Indonesia should be considered more carefully, because there are so many data forgeries carried out by prospective Migrant Workers. The Class I Immigration Office of TPI Yogyakarta can act decisively if there are suspicious things in submitting a passport application. To further improve coordination between the Class I Immigration Office of TPI Yogyakarta and the Distributor of Indonesian Migrant Worker Services related to Indonesian Migrant Workers. Therefore, regular meetings should be held that can be held every month to discuss problems that arise or to find solutions to the problem of illegal migrant workers.